2008
DOI: 10.1261/rna.816908
|View full text |Cite
|
Sign up to set email alerts
|

Screening of human SNP database identifies recoding sites of A-to-I RNA editing

Abstract: Single nucleotide polymorphisms (SNPs) are DNA sequence variations that can affect the expression or function of genes. As a result, they may lead to phenotypic differences between individuals, such as susceptibility to disease, response to medications, and disease progression. Millions of SNPs have been mapped within the human genome providing a rich resource for genetic variation studies. Adenosine-to-inosine RNA editing also leads to the production of RNA and protein sequence variants, but it acts on the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 42 publications
(71 reference statements)
2
31
0
Order By: Relevance
“…11 Additional targets for RNA editing in coding regions were identified by different screens over the last years. 2,11,12,44,45 In agreement with an expected role for editing in brain function and evolution many of these editing sites were found in receptors, ion channels and proteins involved in synapse function, trafficking or membrane organization. 11 The novel targets CyFip2 (Pir121), Filamin A (Flna) and Filamin B (Flnb) are involved in different steps of actin reorganization (Fig.…”
Section: Regulation Of Adar Activitysupporting
confidence: 64%
See 1 more Smart Citation
“…11 Additional targets for RNA editing in coding regions were identified by different screens over the last years. 2,11,12,44,45 In agreement with an expected role for editing in brain function and evolution many of these editing sites were found in receptors, ion channels and proteins involved in synapse function, trafficking or membrane organization. 11 The novel targets CyFip2 (Pir121), Filamin A (Flna) and Filamin B (Flnb) are involved in different steps of actin reorganization (Fig.…”
Section: Regulation Of Adar Activitysupporting
confidence: 64%
“…[1][2][3][4][44][45][46] Most of the predicted editing sites are localized in non-coding regions. Especially the infiltration of the primate genome with Alu elements seems to have led to high editing rates in these elements.…”
Section: Targets For Adenosine To Inosine Editingmentioning
confidence: 99%
“…The Igfbp7 B site 28 is clearly the principal site in this amplicon with 45.6% editing. The same is evident for the Grik2 Q/R site, which has the most pronounced singular editing at 32.1%.…”
Section: Resultsmentioning
confidence: 91%
“…In particular, several methodical prospective surveys of mRNA editing in the human/mammalian transcriptome have strongly suggested that the scale of mRNA editing in the human transcriptome has been seriously underestimated [Blow et al, 2004;Furey et al, 2004;Levanon and Eisenberg, 2006;Gommans et al, 2008]. It is unlikely to be a simple coincidence that the putative example(s) of mRNA editing reported here occurred in an X-linked gene since the hemizygosity of the male patients would have clearly been expected to preclude any signal emanating from the presence of a wild-type IDS sequence, either at the cDNA or the genomic level, at least for the two patients with an inherited IDS gene lesion.…”
Section: Discussionmentioning
confidence: 99%